Offstage Voices : Life in Twin Cities Theater - Guilfoyle, Peg, 1950- (Book collections on Project MUSE., 2015)
"An inside look at Twin Cities theater and how Minneapolis-St. Paul became home to one of the nation's most vibrant and innovative theatrical communities"--